Gesture Meaning of Tortor Used in Simalungun Wedding Ceremony - Nurhasanah Purba; Mulyadi (Britain International for Academic Research (BIAR-Publisher), 2020)
This study discusses about the gesture meaning of tortor in Simalungun Wedding Ceremony. The theory used in this study is McNeill's theory. The data collection was conducted by real work methods it were interviews, documentation and literature study. The methods is used in this study is qualitative method and descriptive approach. The result of this study show that the meaning of totor in simalungun wedding ceremony are showing happiness, respect, compassion, delighted. Each gesture of tortor also serves show a close sense of relationship between two families. In human life, God creates men and women who will have marital relationships and are called husband and wife. With the merging of two families with a marriage, the happiness of both families it show by tortor. Based on McNeill's theory gesture, tortor of Simalungun wedding ceremony included in the types of iconic gesture. This is because the gesture contains a formal relationship.